Bed, bath & bankruptcy : lessons for senior leaders : research reveals that a focus on finances is no substitute for creating customer value when a company is struggling - Knowles, Jonathan; Baris, Russell; Hunsaker, B. Tom; Ettenson, Richard (MIT Sloan Management Review, 2023)
A survey of more than 1,600 Bed Bath & Beyond shoppers reveals why a business recovery strategy set in motion by a new management team in 2019 failed: The BB&B leadership team’s focus on cost cutting overlooked the importance of creating value for customers. The story of the retailer’s bankruptcy is a cautionary tale for other businesses that are struggling to adapt and at risk of losing sight of customer value creation amid increased competition in a changing market.